Adjective Lithuanianisms of the Kursenieki Language in Written Sources - Laurynas Candravičius (Acta Humanitarica Academiae Saulensis, 2023)
In the 15th and 18th centuries, part of the Curonian population moved to the Curonian Spit. The settlers brought their own dialect, which became a separate ethnic minority language when they mixed with Lithuanians, Germans, and descendants of Prussians. It was mainly used in fishing and in fishermen’s homes. It did not have its own script, but various linguists and ethnographers have tried to record it using the scripts of other languages (German, Lithuanian, Latvian). Monuments of the Kursenieki language are sparse. In order to investigate the influence of the Lithuanian language on the adjectival lexis of Kursenieki adjectives from the point of view of etymology, and to examine how the impact of the Lithuanian language on Kursenieki adjectival lexis has changed over the last 150 years, the adjectival inventories of the Kursenieki language at the end of the 19th century, the beginning of the 20th century, and the end of the 20th century are compared in the article. The descriptions of adjectives done by linguists who have studied the Kursenieki language are not exhaustive, as the descriptions of the loanwords of the Kursenieki language from the Lithuanian language tend to focus on nouns and verbs.